2000
DOI: 10.1038/sj.ijo.0801245
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in Brazilian adolescents

Abstract: and 3 Fundac Ëa Äo Seade, Brazil OBJECTIVE: This study aimed to describe the prevalence of overweight and obesity (OW O) among Brazilian adolescents and to identify risks for subpopulations de®ned according to the ®ve country macro-regions and situation (urban±rural) of the domiciles, income, years of school attendance, age and sex. DESIGN: A nationwide home-based survey representative of the Brazilian civilian noninstitutionalized population, performed in 1989. METHODS: The sampling plans followed a strati®ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
45
2
34

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(99 citation statements)
references
References 16 publications
18
45
2
34
Order By: Relevance
“…Although DHS provides data only in girls who have had a child in the previous 3 y (hence a different population), the prevalence of overweight was found to be of a similar size (data not shown). The results described in this paper are furthermore in agreement to previous reports for Brazil (Neutzling et al, 2000) and East Germany (Frye and Heinrich, 2003), but apparently in other countries the contrary is observed (Kautiainen et al, 2002;Savva et al, 2002), where boys tend to be more overweight than girls, hence impeding generalisation.…”
Section: Discussionsupporting
confidence: 92%
“…Although DHS provides data only in girls who have had a child in the previous 3 y (hence a different population), the prevalence of overweight was found to be of a similar size (data not shown). The results described in this paper are furthermore in agreement to previous reports for Brazil (Neutzling et al, 2000) and East Germany (Frye and Heinrich, 2003), but apparently in other countries the contrary is observed (Kautiainen et al, 2002;Savva et al, 2002), where boys tend to be more overweight than girls, hence impeding generalisation.…”
Section: Discussionsupporting
confidence: 92%
“…From these cited studies, it appears that Kuwaiti adolescents take the lead in the level of obesity. With the exception of the Brazilians (Neutzling et al, 2000), the percentages shown do not seem to vary much. In most studies, this one included, the level of fatness among adolescent girls was found to be higher than boys (Forbes, 1977;Neutzling et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
“…With the exception of the Brazilians (Neutzling et al, 2000), the percentages shown do not seem to vary much. In most studies, this one included, the level of fatness among adolescent girls was found to be higher than boys (Forbes, 1977;Neutzling et al, 2000). The risk of obesity among girls in one study was twice as high as among boys (Neutzling et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations